Modeling of substitution augmentation modification redefinition in academic information system education 3.0: a case study of sistem informasi akademik, Universitas Langlangbuana - Utomo, Hadi Prasetyo (2021)
The emergence of Education 3.0 as a new paradigm in education has been spread widely in many educational institutions, especially in higher education institutions (HEIs). Many of them have been implementing Education 3.0, such as socially constructed, technology-oriented, and mobile learning. However, the implementation caused some problems. The new procedures are causing administrative problems, especially in the academic affair (e.g., redundant administrative works, late to submit final marks). The problems also mentioned the mobile access issue. Some information and functionalities missed when accessing the academic information system (AIS) from the mobile device. Moreover, the implementation also needs to provide external involvement (parents and industry). The academic information system (AIS) can be used to support the characteristics of Education 3.0. The information system (IS) components possibly related to the characteristics of Education 3.0. The first phase of this research used a case study of Sistem Informasi Akademik, Universitas Langlangbuana to conduct qualitative research with a semistructured